Comparisons of Auditory Impressions and Auditory Imagery Associated with Onomatopoeic Representation for Environmental Sounds. (11th August 2010) - Takada, Masayuki; Fujisawa, Nozomu; Obata, Fumino; Iwamiya, Shin-ichiro
Abstract : Humans represent sounds to others and receive information about sounds from others using onomatopoeia. Such representation is useful for obtaining and reporting the acoustic features and impressions of actual sounds without having to hear or emit them. But how accurately can we obtain such sound information from onomatopoeic representations? To examine the validity and applicability of using verbal representations to obtain sound information, experiments were carried out in which the participants evaluated auditory imagery associated with onomatopoeic representations created by listeners of various environmental sounds. Results of comparisons of impressions between real sounds and onomatopoeic stimuli showed that impressions of sharpness and brightness for both real sounds and onomatopoeic stimuli were similar, as were emotional impressions such as "pleasantness" for real sounds and major (typical) onomatopoeic stimuli. Furthermore, recognition of the sound source from onomatopoeic stimuli affected the emotional impression similarity between real sounds and onomatopoeia.